Permainan Tradisional Ular Tangga Raksasa Sebagai Wahana Pendidikan Karakter - Siska Oktaviani (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
The purpose of this community service is to increase the value of character in children, and reintroduce the traditional snake and ladder game with a more exciting game pattern so that in the future this traditional game can continue to be carried out by the children of RT .13 Sidodadi Samarinda Ulu Village. The method used in this activity is the preparatory stage with a visit to RT.13 Sidodadi, then the implementation stage of the activity begins with the delivery of material about traditional games in the form of various kinds, benefits and steps of the game demonstrated by the community service team, then the final stage with give rewards given to children who represent the group that made it quickly to the finish line. It is hoped that this giant snake and ladder game can shape character values in children, as well as reintroduce the traditional snake and ladder game with a more exciting game pattern so that in the future this traditional game can continue to be carried out by children in RT.13 Sidodadi to fill their spare time.